HUBUNGAN TINGKAT SOSIAL EKONOMI DENGAN PEMBANGUNAN BERKELANJUTAN DI PPI PANTAI SADENG KABUPATEN GUNUNGKIDUL YOGYAKARTA - Subarno, Anton (MIIPS, 2010)
The Correlation of the Community?s Socio-Economic Level to the EnvironmentBasedDevelopment at the Fish Port of Sadeng Beach, Gunungkidul District, Yogyakarta.The aims of the research were to find out: (1) whether or not there was a correlationbetween the community?s socio economic level and the environment based development, (2) to know the percentage of a correlation between the community?s socio economic level and the environment based development. This is a descriptive research. The location of the research was at Sadeng beach, Gunungkidul district, Yogyakarta. The populations of the research were 6149 people and the samples of the research were 362 people. The data analyzing by using a regression analysis with prerequisite tests of normality test and linearity test. Based on the results of the analysis, conclusions are drawn as follows: (1) there is a positive and significant correlation between the community?s economic level and the environment-based development at the fish port of Sadeng beach (r x1y o = 0.867 P<0.5) and t o = 32.971 P < 0.05), (2) the percentage of a correlation between the community?s socioeconomic level and the environment based development at the fish port of Sadeng beach is75.1 %